Improving Speaking Skills of Santri through Drilling Technique and Cinema Therapy in Group Counseling of Bakmin Program - Halimatus Sa’diyah; Suhono Suhono; Wiwied Pratiwi; Kushendar Kushendar; Sugiarto Sugiarto (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
The purpose of this research was to find out the Improving Speaking Skills of Santri through Drilling Technique and Group Counseling, that was Cinema Therapy technique of Bakmin Program at Boarding School Wali Songo Sukajadi. The researchers used a classroom action research. The data collection technique used observation, test, and documentation study. The research findings showed that Students speaking ability improved by using repetition drill from the cycle to cycle. At the first cycle, the writer did not get the students to score. The second cycle was 68,75, and the last cycle was 80,08. In the first cycle, the writer did not get the students to score because there were some problems that happened in this cycle. Through the second cycle, students competences step by step were increased. In the last cycle, students showed significant progress to the result. It gave the writer a substantial that the speaking ability improved.